Acceptance of freshwater fish meal among students in Universiti Kebangsaan Malaysia - Razalee Sedek; Nor Farhana Mohd Samwil (penerbit ukm, 2014)
Various efforts and campaigns have been carried out by the government to encourage the acceptance of freshwater fi sh meal by the public. The objectives of this study were to assess the acceptance of Universiti Kebangsaan Malaysia (UKM) students towards freshwater fi sh meal and to determine the factors that infl uence freshwater fi sh meal intake. A total of 232 students were randomly chosen from faculties in UKM (Bangi campus). Besides of students, food handlers of UKM’s Cafeteria were also involved in this study. Questionnaire were used to assess level of understanding and acceptability of students towards freshwater fi sh, frequency of freshwater fi sh meal intake and the factors that affect their intake. The extent of availability and variety of freshwater fi sh meal was identifi ed by observations at selected cafeterias in UKM. Majority of respondents (95.7%) were aware of freshwater fi sh in general but only 55.6% of the respondents know the type or species of freshwater fi sh. Results showed that majority of respondents (63.3%) choose fresh water fi sh as meal. Chi Squared Test showed that there were signifi cant associations between religion and race with respondents’ selection of freshwater fi sh as a meal (p < 0.05). Catfi sh (51.9%) was the most prefered fresh water fi sh by respondents. Meals most favored by majority of respondents (36.2%) were fried freshwater fi sh. Majority of respondents (43.2%) like to eat freshwater fi sh due to the taste factor. Most cafeterias in UKM sell freshwater fi sh dishes. This is mainly because they want to add variation in the menu sold in their cafeterias. A total of 69.2% of the cafeterias reported students’ acceptance on freshwater fi sh meals were very good but only for selected freshwater fi sh meal. This study provides useful information to the government on the acceptibility and awareness among university students towards freshwater fi sh and also to assist food handler of UKM’s Cafeteria in preparation of freshwater fi sh meals that are suitable with the students’ preference.